Baghdad or Bust : The Inside Story of Gulf War 2 - Ryan, Mike (South Yorkshire Leo Cooper, 2003)
"[This book details] the ... joint US and UK campaign to liberate Iraq from the oppressive regime of Saddam Hussein from its conception to ... conclusion ... [The author] examines the logistical and political problems ... and the ... tensions and manoeuvring behind the scenes conducted under the conditions of extreme pressure and secrecy ... This book also delves into those curses of modern warfare, friendly fire incidents, and collateral damage, and why, even with all the marvels of modern technology, we still cannot prevent tragedies [from] happening"--Jacket.
Include Illustrations and Index
Keywords: Iraq War (2003-2011) -- Strategy